Immediate microleakage in direct and indirect restorative procedures - Cruz, J. Nunes da (2018)
Poster presented at the CED-IADR/NOF Oral Health Research Congress (2017 Continental European and Scandinavian Divisions Meeting). September 21-23, 2017. Vienna, Austria